The influence of Malay cultural beliefs on breast cancer screening and genetic testing: A focus group study. Issue 12 (16th October 2018) - Shaw, Tarryn; Ishak, Diana; Lie, Désirée; Menon, Sapna; Courtney, Eliza; Li, Shao‐Tzu; Ngeow, Joanne
Abstract: Objective: Malays comprise an Asian cultural group reported to have low breast cancer screening uptake rates and poor cancer outcomes. Little is known about Malay cultural factors influencing beliefs and practice of cancer screening and genetic testing. Our study aims to explore health beliefs of Malay women around breast cancer screening and genetic testing. Methods: We conducted focus groups among healthy English‐speaking Malay women in Singapore, aged 40 to 69 years, using a structured guide developed through literature review, expertise input and participant refinement. Thematic analysis was conducted to extract dominant themes representing key motivators and barriers to screening and genetic testing. We used grounded theory to interpret results and derive a framework of understanding, with implications for improving uptake of services. Results: Five focus groups (four to six participants per group) comprising 27 women were conducted to theme saturation. Major themes were (a) spiritual and religious beliefs act as barriers towards uptake of screening and genetic testing; (b) preference for traditional medicine competes with Western medicine recommendations; (c) family and community influence health‐related decisions, complexed by differences in intergenerational beliefs creating contrasting attitudes towards screening and prevention. Conclusions: Decisions to participate in breast cancer screening and genetic testing are influenced by cultural, traditional, spiritual/religious, and intergenerational beliefs. Strategies to increase uptake should include acknowledgement and integration of these beliefs into counseling and education and collaboration with key influential Malay stakeholders and leaders.